THE IMPACT OF CELEBRITY ENDORSEMENTS IN INDIA - Khan, Shahira (2011)

(untitled)
The technique of using celebrities to endorse a company’s product has been in use for many decades now. The absolute popularity of this strategy is explained by the presence of a known face in every second commercial on the television. This line of attack has been used to grab the attention of potential target audience in a highly cluttered market characterised by n number of brands and their offerings. A lot has been written and tested about this approach in the western countries, considering them as a source of origin of this technique, but a little is known academically in a country like India. Being the third largest economy in Asia, and one of the most promising markets in the world, marketers in order to fight off competition extensively deploy this technique in almost all possible categories of products ranging from a mere pen to a complicated car. The aim of any strategy used by the marketers is ultimately aimed at securing the attention of the end user, but it is not necessary that the consumer will always understand and respond to these efforts. Some product categories like house hold items, groceries, toiletries also use this technique but it is not essential that the final user in this case the house wives understand it. This dissertation is an attempt to analyse how the house makers think and react towards the concept of celebrity endorsements and their subsequent behaviour as a buyer. This study begins with a literature review which sets a foundation of the research by providing an insight to the knowledge already created on this topic by various academicians and authors. Then follows the research methodology which in this case happens to be in depth interviews with housewives, which is the most appropriate way of striking a balance between the theory and this particular segment of the society. The data so gathered is thoroughly analysed which has led the purpose of the study to some very interesting outcomes, which are summarised under conclusions and hence setting the base for managerial implications.